2008
DOI: 10.1242/jeb.005736
|View full text |Cite
|
Sign up to set email alerts
|

Free-flight encounters between praying mantids (Parasphendale agrionina) and bats (Eptesicus fuscus)

Abstract: SUMMARYThrough staged free-flight encounters between echolocating bats and praying mantids, we examined the effectiveness of two potential predator-evasion behaviors mediated by different sensory modalities: (1) power dive responses triggered by bat echolocation detected by the mantis ultrasound-sensitive auditory system, and (2) ʻlast-ditchʼ maneuvers triggered by batgenerated wind detected by the mantis cercal system. Hearing mantids escaped more often than deafened mantids (76% vs 34%, respectively; hearing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
3
26
1
Order By: Relevance
“…Studies of bats attacking insects around lights have typically not quantified the effects of lights on moth behavior and on the outcome of interactions (Acharya and Fenton, 1992;Acharya and Fenton, 1999;Rydell, 1992). In the present study (where 15W ultraviolet lights were used) we found no such effect, as the percentages of moths diving and being captured were independent of moth distance to ultraviolet lights (Fig.5) (Rydell, 1992); 4 Acharya and Fenton (Acharya and Fenton, 1999); 5 Triblehorn (Triblehorn et al, 2008); 6 present study; and 2004). We conclude that the use of low-wattage ultraviolet lights appears to be a valid method for attracting naturally behaving bats and moths for study.…”
Section: Moth Proximity To Ultraviolet Lights Does Not Inhibit Defenscontrasting
confidence: 38%
See 1 more Smart Citation
“…Studies of bats attacking insects around lights have typically not quantified the effects of lights on moth behavior and on the outcome of interactions (Acharya and Fenton, 1992;Acharya and Fenton, 1999;Rydell, 1992). In the present study (where 15W ultraviolet lights were used) we found no such effect, as the percentages of moths diving and being captured were independent of moth distance to ultraviolet lights (Fig.5) (Rydell, 1992); 4 Acharya and Fenton (Acharya and Fenton, 1999); 5 Triblehorn (Triblehorn et al, 2008); 6 present study; and 2004). We conclude that the use of low-wattage ultraviolet lights appears to be a valid method for attracting naturally behaving bats and moths for study.…”
Section: Moth Proximity To Ultraviolet Lights Does Not Inhibit Defenscontrasting
confidence: 38%
“…Research documenting the pursuit and escape flight of bats and insects has largely been restricted to captive animals in controlled environments (Corcoran et al, 2010;Dawson et al, 2004;Ghose et al, 2006;Ghose et al, 2009;Triblehorn et al, 2008). Although these laboratory studies have yielded many novel discoveries, the limited space of a flight room prevents the animals from exhibiting the full suite of behaviors that occur in nature.…”
Section: Introductionmentioning
confidence: 99%
“…It was not possible to determine how much of this variation came from differences between or within species, but an exciting future direction is examining how species-specific escape strategies relate to differences in flight morphology and turning ability. Moths and other insects often make dives when pursued by bats (Roeder, 1962;Triblehorn et al, 2008;Corcoran and Conner, 2012). A key component of this strategy may be using gravity to increase radial acceleration.…”
Section: Escape Rule 1: Maximize Radial Accelerationmentioning
confidence: 99%
“…Behavioral observations of hunting barbastelles are required to determine whether prey evade too late or not at all. A rapid transition in bat echolocation behavior from search to buzz prevented mantids (Parasphendale agrionina) from initiating defensive responses (Triblehorn et al, 2008), so it may also be possible for bats that echolocate at high intensity to manipulate prey behavior.…”
Section: Escape Rule 1: Maximize Radial Accelerationmentioning
confidence: 99%
See 1 more Smart Citation